Theoretical Study of the Use of Cyano Acid Derivatives as Electron Acceptors in Cyanidin as Compounds of Dye Sensitized Solar Cells (DSSC) - Muhammad Nur Maulidin Mahmud; Sudarlin Sudarlin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Theoretical study of the use of cyano acid derivatives as electron acceptor groups in cyanidine as dye compounds of dye sensitized solar cells (DSSC) has been carried out based on energy parameters of HOMO-LUMO, LUMO electron localization, spectra, light absorption efficiency, coupling constants, and sensitizer bond length with TiO2. This study aims to determine the effect of cyanoacetic acid, cyanoacrylic benzothiadizole, cyanovinyl acid and cyanosynamic acid as electron acceptors on the photoelectric characteristics of cyanidine and determine the cyanoic acid derivative which can produce cyanidine photoelectric characteristics better based on energy parameters HOMO-LUMO, LUMO electron localization, spectra, light harvesting efficiency, coupling constant (VRP), and bond length of sensitizer with TiO2. This research begun with molecular optimization using DFT and TDDFT method with basis set of 6.311G *. HOMO-LUMO parameters used the same method with analysis technique using ECCE. The LUMO electron localization parameters use the same method, but the analysis technique used ECCE. Spectra using DFT method, using analytical technique using Chemcraft. Parameters of light absorption efficiency using DFT and TDDFT method with calculation technique using existing equations. Coupling constant parameters using the same method, the calculation technique used the energy equation of dye compounds were calculated in the conditions of HOMO, LUMO and TiO2 energy. Parameter length of the sensitizer bond with TiO2 were calculated used DFT method with avogadro analysis technique. Cyanidin cyanoacetate became the best modification based on HOMO LUMO energy parameter -4.569 and -1.01 eV, respesctively. In the electron localization parameter, the best modification was produced in cyanidine cyanoacetate with an electron-centered pattern on the cyanoacetic group. Spectra parameters produced the best modification, cyanoacetic cyanidine with a wavelength of 378.811 nm with osillator strength of 0.633. The light absorption efficiency parameters resulted in the best modification of cyanidin cyanoacetate with a value of 0.767. For parameter of clutch constant, best modification is cyanidin benzothiadizol sianoakrilik with a value -0.269. The best modification on the parameter length of the sensitizer bond with TiO2 was cyanidine cyanoacetate with a bond length of 1.926 Å.